Impact of socioeconomic status in patients hospitalised for COVID-19 in the Greater Paris area. Issue 6 (24th December 2020) - Sesé, Lucile; Nguyen, Yann; Giroux Leprieur, Etienne; Annesi-Maesano, Isabella; Cavalin, Catherine; Goupil de Bouillé, Jeanne; Demestier, Louis; Dhote, Robin; Tandjaoui-Lambiotte, Yacine; Bauvois, Adeline; Pépin, Marion; Curac, Sonja; et al.
In the USA, coronavirus disease 2019 (COVID-19) is more likely to affect and kill African Americans [1], which raises the question of the contribution of several factors, including genetic background, socioeconomic status (SES), and comorbidities [2]. According to the French National Institute of Statistics and Economic Studies (INSEE) the highest excess mortality rate in France, during March and April 2020, linked to COVID-19 was found in the Seine-Saint-Denis (SSD) district [3]. SSD is the poorest district of Greater Paris [4]. We hypothesise that precarity influences the initial severity of COVID-19. Individual precarity seems to be associated with the initial severity of COVID-19 in hospitalised patients under the age of 70 years. Low socioeconomic status may contribute to the excess mortality observed in the poorest district of Greater Paris. https://bit.ly/3kuStXS